Case report: Percutaneous adrenal arterial embolization cures resistant hypertension - Zhou, Yaqiong; Wang, Dan; Liu, Qiting; Hou, Jixin; Wang, Peijian (Frontiers in Cardiovascular Medicine, 2022)
Background: Primary aldosteronism is a common cause of resistant hypertension. Patients with primary aldosteronism due to aldosterone-producing adenoma are generally treated with unilateral adrenalectomy or medical therapy. Superselective adrenal arterial embolization is an alternative treatment for patients with unilateral primary aldosteronism. Case summary: We present a 39-year-old male patient with a 5-year history of primary aldosteronism and secondary hypertension. The patient refused adrenalectomy while accepted pharmacotherapy. Despite taking adequate dose of spironolactone, the patient experienced repeatedly muscle weakness due to hypokalemia and had poor blood pressure control with left ventricular hypertrophy and renal dysfunction. Aldosterone-producing adenoma in the left adrenal gland was confirmed by computerized tomography and adrenal venous sampling. The left middle adrenal artery, which was confirmed to provide the main arterial supply to the aldosterone-producing adenoma, was embolized by injecting 2 mL ethanol. The embolization normalized his blood pressure for up to 3 months and reversed left ventricular hypertrophy. Conclusions: Superselective adrenal arterial embolization could be an alternative treatment for patients with aldosterone-producing adenoma who refuse adrenalectomy.